Analisis Pengaruh Profitabilitas Terhadap Harga Saham Pada Perusahaan Perbankan Yang Terdapat Di BEI Pada Periode 2011-2014 - Prihandani, Aninda Mahar; , Sri Murwanti, SE, MM (2016)
This study aimed to analyze the effect on stock prices on the profitability of banks listed companies in Indonesia Stock Exchange (BEI) in 2011-2014. In connection with the research objectives, the proposed research hypotheses that affect the profitability ratio of stock prices to corporate banking listed in the Indonesia Stock Exchange (BEI) in 2011-2014. This study uses a survey of secondary data with the population of banking companies listed on the Indonesian Stock Exchange (BEI) in 2011-2014. Criteria used to determine the sample with purposive sampling method this is a company whose shares are actively traded during the year 2011-2014, published financial statements. With this method obtained a sample of 19 companies. This study uses a measurement tool of corporate profitability is Return On Assets (ROA), Return on Equity (ROE), and the Net Profit Margin (NPM). The analytical method used is multiple regression model. Hypothesis testing is done by using t-test that tests the influence of independent variables are Return On Assets (ROA), Return on Equity (ROE), and the Net Profit Margin (NPM) partially to the stock price, and the F-test that tests the analysis of the influence of the ratio profitability together (simultaneously) on the dependent variable is the stock price. The results using test Regression is concluded that the partial Return On Assets have a significant influence on stock prices, (2) Return on Equity has a significant influence on stock prices, (3) Net Profit Margintidak have a significant influence on stock prices the banking company listed on the Indonesia Stock Exchange (BEI) in 2011-2014.